2007
DOI: 10.1093/ecam/nem159
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Therapy of Cancer with Ascorbate and Extracts of Medicinal Herbs

Abstract: Catalytic therapy (CT) is a cancer treatment modality based on the generation of reactive oxygen species (ROS) using a combination of substrate molecules and a catalyst. The most frequently used substrate/catalyst pair is ascorbate/Co phthalocyanine (PcCo). In the present work, herb extracts containing pigments have been studied as a catalyst in place of PcCo. Extracts from herbs are expected to have efficiency comparable with that of phthalocyanines but as natural products, to exhibit fewer side effects. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…The selection process of the systematic search and numbers of included and excluded papers are presented in Figure 1. In total, 43 full text articles were assessed for eligibility, of which 17 [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] were excluded based on reasons given in Figure 1. At the end of the selection process, 26 articles were considered eligible for this review.…”
Section: Resultsmentioning
confidence: 99%
“…The selection process of the systematic search and numbers of included and excluded papers are presented in Figure 1. In total, 43 full text articles were assessed for eligibility, of which 17 [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] were excluded based on reasons given in Figure 1. At the end of the selection process, 26 articles were considered eligible for this review.…”
Section: Resultsmentioning
confidence: 99%
“…IV ascorbate but not oral vitamin C produced plasma concentrations sufficiently high (300 – 20,000 μM) to encounter pro-oxidant effect in the extracellular milieu, thus is able to deliver treatment for diseases in which peroxide may have a therapeutic role, such as cancer or infections [79]. High-dose IV ascorbate is widely adopted in the CAIM community [16]. About 10,000 patients per year in US are using IV ascorbate, with an average dose of 28 grams/injection and 22 total doses per patients [4].…”
Section: Discussionmentioning
confidence: 99%
“…For many years, high-dose intravenous (IV) ascorbate (Vitamin C or ascorbic acid) has been used by complementary, alternate and integrative medicine (CAIM) practitioners to treat various conditions including infections, cancer, autoimmune diseases and illnesses of uncertain origin [16]. Clinical use of IV ascorbate is growing as recent studies revealed the scientific basis for this use [4, 710].…”
Section: Introductionmentioning
confidence: 99%
“…In healthy humans, Rehman and colleagues observed an increased level of oxidative DNA damage after 6-week supplementation of a mixture of ferrous sulphate andvitamin C, suggesting that this combination acts as a pro-oxidant; however, a longer period of supplementation by 12 weeks did not show significant effect [ 174 ]. Intriguingly, catalytic therapy that involves hydroxyl radical induction through a redox active mixture of vitamin C/medicinal herbal extracts and copper has been employed to improve the treatment of cancer patients [ 175 , 176 ]. The Bhat group that established a model that involves human peripheral lymphocytes and comet assay carried out a series of studies on plant-derived polyphenolic antioxidants and proved that the mechanism is not restricted to vitamin C [ 177 179 ].…”
Section: “Double-edged Sword” Role Of Phytoagents As Redox Regulatmentioning
confidence: 99%